Effect of Age and Diabetes on the Response of Mesenchymal Progenitor Cells to Fibrin Matrices - A. Stolzing; H. Colley; A. Scutt (International Journal of Biomaterials)
Mesenchymal stem cells are showing increasing promise in applications such as tissue engineering and cell therapy. MSC are low in number in bone marrow, and therefore in vitro expansion is often necessary. In vivo, stem cells often reside within a niche acting to protect the cells. These niches are composed of niche cells, stem cells, and extracellular matrix. When blood vessels are damaged, a fibrin clot forms as part of the wound healing response. The clot constitutes a form of stem cell niche as it appears to maintain the stem cell phenotype while supporting MSC proliferation and differentiation during healing. This is particularly appropriate as fibrin is increasingly being suggested as a scaffold meaning that fibrin-based tissue engineering may to some extent recapitulate wound healing. Here, we describe how fibrin modulates the clonogenic capacity of MSC derived from young/old human donors and normal/diabetic rats. Fibrin was prepared using different concentrations to modulate the stiffness of the substrate. MSC were expanded on these scaffolds and analysed. MSC showed an increased self-renewal on soft surfaces. Old and diabetic cells lost the ability to react to these signals and can no longer adapt to the changed environment.